Variation in fibre morphology and porosity of rubberwood (hevea brasiliensis) / Suhaimi Muhammed and Mohd. Hamami Sahri - Muhammed, Suhaimi; Sahri, Mohd Hamami (Universiti Teknologi MARA Cawangan Pahang, 2000)
Fibre morphology and porosity were determined in rubberwood from two clones and two age groups. Fibre diameter increased from pith to bark but no significant difference between the two clones for the same age group. Similarly, lumen diameter increased from pith to bark. Clone RRIM 600 showed bigger lumen diameter than RRIM 623. Cell wall thickness also increased with increasing distance from the pith. Between age group, the cell wall thickness was significant for clone RRIM 623 but not significant for RRIM 600. Pore diameter increased from pith to bark but pore frequency exhibited a decreasing pattern. Between clone and within clone at both age groups, pore diameter and frequency showed no significant difference. The variation of such properties could serve as a guide in predicting specific end purposes.